Cryopreservation of Primary Mouse Neurons: The Benefit of Neurostore Cryoprotective Medium - Pischedda, Francesca; Montani, Caterina; Obergasteiger, Julia; Frapporti, Giulia; Corti, Corrado; Rosato Siri, Marcelo; Volta, Mattia; Piccoli, Giovanni (Frontiers in Cellular Neuroscience, 2018)
Primary neuronal culture from rodents is a well-established model to investigate cellular neurobiology in vitro. However, for this purpose cell cultures need to be generated expressly, requiring extensive animal handling. Furthermore, often the preparation of fresh culture generates an excess of cells that are ultimately wasted. Therefore the ability to successfully cryopreserve primary neural cells would represent an important resource for neuroscience research and would allow to significantly reduce the sacrifice of animals. We describe here a novel freezing medium that allows long-term cryopreservation of primary mouse neurons prepared from E15.5 embryos. Combining imaging, biochemical and electrophysiological analyses, we found that cryopreserved cultures are viable and mature regarding morphology and functionality. These findings suggest that cryopreserved neurons are a valuable alternative to acutely dissociated neural cultures.